2010
DOI: 10.1177/0961203310379870
|View full text |Cite
|
Sign up to set email alerts
|

Total serum IgE levels in systemic lupus erythematosus and associations with childhood onset allergies

Abstract: Elevated serum IgE has been described in systemic lupus erythematosus (SLE), but associations with disease risk and characteristics remain unresolved. We assessed total serum IgE levels and atopy (IgE > 100 IU/ml) in recently diagnosed SLE patients (n = 228) compared with population controls (n = 293) and in relation to disease activity, autoantibodies, clinical features, total immunoglobulins, C-reactive protein, and allergy history. Multivariate models estimated determinants of IgE and atopy in patients and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
26
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 44 publications
3
26
0
Order By: Relevance
“…Several studies also indirectly consider this relationship by examining autoimmune disease in relation to allergies and asthma, which showed positive associations [31, 32]. However, some studies report an inverse association of childhood farm exposure to animals and grains with SLE, suggesting the possible operation of hygiene hypothesis [33, 34]. There are some possible explanations for these inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies also indirectly consider this relationship by examining autoimmune disease in relation to allergies and asthma, which showed positive associations [31, 32]. However, some studies report an inverse association of childhood farm exposure to animals and grains with SLE, suggesting the possible operation of hygiene hypothesis [33, 34]. There are some possible explanations for these inconsistent findings.…”
Section: Discussionmentioning
confidence: 99%
“…Previous study considered that examining determinants of IgE levels in SLE patients had limited number of patients and controls [35]; thus, their findings are inconclusive. Total IgE levels in allergic individuals may reflect the potential for antigen-specific IgE production associated with hypersensitivity reactions [33,34]. These studies utilize total serum IgE to test IgE-mediated allergies.…”
Section: Discussionmentioning
confidence: 99%
“…IgE may play a role in the active phase of SLE [3], but Parks et al assessed total serum IgE levels and atopy in SLE patients and found no evidence of an independent association between the IgE levels and SLE [18]. The immunological hallmark of IgE-mediated allergy is IgE sensitization, which in the vast majority of epidemiological studies has been found to be more common in males than in females [19].…”
Section: Discussionmentioning
confidence: 99%
“…Smoking and drinking were defined as use at least once a week regularly for 1 year. We defined atopy as total IgE ≥100 IU/ml [25,26]. Waist and hip circumference measurements, whole blood sample collection, a lung function test and DNA genotyping were performed.…”
Section: Methodsmentioning
confidence: 99%